2023
DOI: 10.1186/s12889-023-15345-z
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in colorectal cancer screening uptake in Wales: an examination of the impact of the temporary suspension of the screening programme during the COVID-19 pandemic

Abstract: Background Response to the early stages of the COVID-19 pandemic resulted in the temporary disruption of cancer screening in the UK, and strong public messaging to stay safe and to protect NHS capacity. Following reintroduction in services, we explored the impact on inequalities in uptake of the Bowel Screening Wales (BSW) programme to identify groups who may benefit from tailored interventions. Methods Records within the BSW were linked to electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…One study from Wales reported low uptake of bowel cancer screening by males, younger individuals and those living in areas of higher deprivation. 23 Uptake also varied according to ethnic group, with uptake lowest in those of Asian and Unknown ethnic background, though these findings were comparable before and after the suspension of services because of the COVID-19 pandemic. 23 …”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…One study from Wales reported low uptake of bowel cancer screening by males, younger individuals and those living in areas of higher deprivation. 23 Uptake also varied according to ethnic group, with uptake lowest in those of Asian and Unknown ethnic background, though these findings were comparable before and after the suspension of services because of the COVID-19 pandemic. 23 …”
Section: Discussionmentioning
confidence: 89%
“… 23 Uptake also varied according to ethnic group, with uptake lowest in those of Asian and Unknown ethnic background, though these findings were comparable before and after the suspension of services because of the COVID-19 pandemic. 23 …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Seven studies [ 31 , 32 , 36 , 39 , 58 , 65 , 74 ] scored 1 point because of statistical differences in the most or second-most important factors. Forty-five studies [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , 33 , 34 , 37 , 38 , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [53] , [54] , [55] , [56] , [57] , [59] , [60] , [61] , [62] , [63] , [64] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , 75 , 76 ] scored 0 point in view of the lack of control over the most or second-most important factors in the comparability domain.…”
Section: Resultsmentioning
confidence: 99%
“…2028 There are data accumulating to suggest that the effect of the COVID-19 pandemic has been more pronounced among subjects with low SES, minorities, and those in rural areas in many countries. 15,23,27,2939 However, little is known about the impact of inequalities and the pandemic on CRC screening within an organization with universal health insurance.…”
Section: Introductionmentioning
confidence: 99%